Physical Literacy, Fitness, and Multidimensional Health Outcomes among MPhil Scholars in Sports Sciences: A Comparative Cross-Sectional Study of Cohorts at Health Services Academy, Islamabad - LUQMAN, MUHAMMAD SAFDAR; ABBAS, SYED ASIF; RAUF, ADEELA; RAZZAQ, FOUZIA ABDUL (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Physical literacy has been widely acknowledged as the determinant of physical fitness and multidimensional health outcomes, which are usually among the students undertaking sports sciences programs. Nevertheless, there are a few studies on the impact of academic advancement on such parameters among postgraduate scholars. Objective: To describe differences between first-year and second-year MPhil students in sports sciences in physical literacy, physical fitness, and multidimensional health outcomes, and to investigate predictive ability of physical literacy in all health-related outcomes. Methods: The study was a comparative cross-sectional study carried out on 52 MPhil students of sports sciences in the Health Services Academy, Islamabad. The participants were separated into two groups, the first year (n = 28) and the second year (n = 24). The PLAY-self questionnaire was taken to measure physical literacy, field-based tests (aerobic capacity, flexibility, and muscular endurance) to measure physical fitness and the Duke Health Profile and the Spiritual Well-Being Scale to measure health outcomes. The difference between the group was compared with the independent t-tests, and regression analyses were achieved to determine the predictive associations between the physical literacy and health domains. Results: Population On average, physical literacy (M = 76.1 vs. 68.2, p =.014, d=0.72), aerobic capacity (2,450 m vs. 2,210 m, p =.006, d=0.81), flexibility (28.4 cm vs. 24.7 cm, p =.012, d=0.74), physical health (78.5 vs. 70.2, p=.018, d=0 There were no significant differences in the muscular endurance, social health or spiritual health. Physical literacy turned out to be a precursor to all the health areas (= 33- 42, p <. 01), with the higher association between first-year scholars especially with psychological health (=.041). Conclusion: The advancement of academics can be linked to physical literacy, choice of fitness elements and psychological health deterioration among scholars in sports sciences. The implementation of early-stage, curriculum-based wellness interventions would allow preserving embodied and psychological wellness among students during postgraduate training.